Characterizations of volatile organic compounds (VOCs) from vehicular emissions at roadside environment: The first comprehensive study in Northwestern China. (July 2017) - Li, Bowei; Ho, Steven Sai Hang; Xue, Yonggang; Huang, Yu; Wang, Liqin; Cheng, Yan; Dai, Wenting; Zhong, Haobin; Cao, Junji; Lee, Shuncheng
Abstract: Vehicular emission (VE) is one of the important anthropogenic sources for ground-level volatile organic compounds (VOCs) in both urban and suburban areas. A first comprehensive campaign was conducted at an urban roadside in Xi'an, China in summer, 2016. A total of 57 VOCs, as known as critical surface ozone (O3 ) precursors, and other trace gases were measured simultaneously during the sampling period. Iso -pentane, a tracer of gasoline evaporation, was the most abundant VOC in the roadside samples, followed by isobutane and benzene, attributed to the largest composition (∼70%) of gasoline-fueled vehicles on the road. The molar ratio of toluene/benzene (T/B) in our study (0.36) is far lower than the range reported in other cities, indicating the stronger contributions from diesel emissions. The results of source apportionment achieved with positive matrix factorization (PMF) receptor model were highly consistent with the vehicles compositions, strongly evidenced that the precise characterization of the VE sources from those marker species. The degrees of individual compound contributed to O3 production were weighed by ozone formation potential (OFP). Propylene (20%), 1-butene (11%) and iso -pentane(10%) were the top three contributors at the roadside. The information of this study complements the VOCs database regarding to the VE sources in Northwestern China. Graphical abstract: Highlights: VOCs have been quantified at a roadside environment in Xi'an, China first time. Isopentane was the most abundant compound in the traffic-dominated environment. Different vehicular sources were resolved by a receptor model. Compressed natural gas (CNG) combustion has a distinct impact on ozone formation. Abstract : Illustrate the current composition and the major emission sources of VOCs at the roadside environment in northwest China, and discuss their impacts on ozone formation.